The Development of a Hybrid Underwater Micro Biped Robot - S. Guo; Y. Okuda; W. Zhang; X. Ye; K. Asaka (Applied Bionics and Biomechanics, 2006)
There has been a great demand, in the medical field and in industrial applications, for a novel micro biped robot with multiple degrees of freedom that can swim smoothly in water or in aqueous medium. The fish-like micro-robot studied is a type of miniature device that is installed with sensing and actuating elements. This article describes the new structure and motion mechanism of a hybrid type of underwater micro-robot using an ion-conducting polymer film (ICPF) actuator, and discusses the swimming and floating characteristics of the micro-robot in water, measured by changing the voltage frequency and the amplitude of the input voltage. Results indicate that the swimming speed of the proposed underwater micro-robot can be controlled by changing the frequency of the input voltage, and the direction (upward or downward) can be manipulated by changing the frequency of the electric current applied and the amplitude of the voltage.